Studi Kejadian Efek Samping Pengobatan Rheumatoid Arthitis Pasien Rawat Jalan Di Rumah Sakit Ulin - Wahyu Pangi Astuti, Ni Nyoman; Kurniawati, Darini; Mustaqimah, Mustaqimah (CV. Wadah Publikasi Cendekia, 2023)
Background: Rheumatoid Arthritis (RA) is an autoimmune disease in the form of chronic inflammation and can cause permanent joint damage. Currently it is estimated that no less than 1.3 million people suffer from Rheumatoid Arthritis (RA) in Indonesia at the calculation. RA in Indonesia, can increase the use of RA drugs which affect the incidence of drug side effects. So it is necessary to study the use of drugs in terms of side effects of RA drugs using the Naranjo Algorithm Objective: This study aims to determine the incidence of side effects that occur in RA patients and identify the occurrence of drug side effects by analyzing the Naranjo scale Methods: This research uses a descriptive observational method with a prospective cross sectional approach using the Naranjo Algorithm questionnaire as an instrument. Results: The results showed that of the 58 respondents who were interviewed, 21 respondents felt side effects in the form of 18 respondents including nausea, vomiting, dizziness and 3 respondents Alopecia, 20 respondents included in the Definite category and 1 respondent included in the Probable category Conclusion: Side effects that occur may be caused by suspected Rheumatoid Arthritis (RA) drugs, namely DMARDs and NSAIDs. Keywords: Naranjo Algorithm, Side Effects, Rheumatoid Arthritis